2011
DOI: 10.1136/bjsm.2010.081695
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring strain injuries: are we heading in the right direction?

Abstract: Acute hamstring injuries are the most prevalent muscle injuries reported in sport. Despite a thorough and concentrated effort to prevent and rehabilitate hamstring injuries, injury occurrence and re-injury rates have not improved over the last three decades. This failure is most likely due to the following: (1) a lack of studies with high level of evidence into the identifi cation and prevention of hamstring injuries and (2) a reductionist approach of the current literature. The objectives of this article are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
25

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 101 publications
(122 reference statements)
1
141
0
25
Order By: Relevance
“…Horizontal force development is higher during the acceleration phase (figure 2) and has been correlated with performance variables related to acceleration, rather than those related to steady state sprinting [17]. For that reason it was hypothesised that any injury-related differences in horizontal force performance were more likely to be present in this phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal force development is higher during the acceleration phase (figure 2) and has been correlated with performance variables related to acceleration, rather than those related to steady state sprinting [17]. For that reason it was hypothesised that any injury-related differences in horizontal force performance were more likely to be present in this phase.…”
Section: Discussionmentioning
confidence: 99%
“…Hamstrings also present a high recurrence rate of 12-14% [20,28], and re-injury on average requires six days longer absence from competition than the initial injury [6]. In fact, previous injury remains to be the strongest available predictor for hamstring injury [2,8,9,17,22,28].…”
Section: Introductionmentioning
confidence: 99%
“…It seems appropriate to direct future investigations toward HSI management that incorporates various multimodal strategies to identify the optimal HSI plan that achieves the best patient outcomes. 80 Whereas many other prevalent sport-related injuries, such as anterior cruciate ligament tears and ankle sprains, have well-developed evidence-based protocols available for use as clinical practice guidelines, 81-83 a protocol for managing HSIs has not been established. An evidence-based approach is needed for HSI management to decrease the high injury rates plaguing athletes at this time.…”
Section: Beliefs Associated With Treatment and Rehabilitation Methodsmentioning
confidence: 99%
“…Notably, Petersen et al [50] demonstrated a significant reduction of approximately 85%. This is particularly relevant given that previous injury is the greatest risk factor for hamstring strain [68] and that re-injuries cause longer absences from sport [5].…”
Section: Summary Of Evidencementioning
confidence: 99%